1985
DOI: 10.1177/0022427885022004002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residential Treatment on Adjudicated Delinquents: A Meta-Analysis

Abstract: Recent trends toward a more punitive approach to juvenile crime have been heavily influenced by a body of review literature that reports that the traditional treatment approach is ineffective. The opinion that “nothing works” is largely based on reviews of the treatment literature. These reviews generally fail to document the amount of change associated with treatment. A meta-analysis of the primary research literature produced since 1960 was undertaken to assess the amount of change associated with various tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
0
10

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(133 citation statements)
references
References 15 publications
3
120
0
10
Order By: Relevance
“…Several literature reviews and meta-analyses draw this conclusion, stating that a change in the offender's thinking must take place for behavior change to occur (Greenwood, 2002;Mihalic, Irwin, Elliott, Fagan, and Hansen, 2001;MacKenzie, 2000;Izzo and Ross, 1990;Andrews 1990, Ross andFabiano, 1985;Garrett, 1985). In several cases this conclusion is quite strong, for example, Izzo and Ross (1990) found that programs containing a cognitive element were twice as effective as those that did not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several literature reviews and meta-analyses draw this conclusion, stating that a change in the offender's thinking must take place for behavior change to occur (Greenwood, 2002;Mihalic, Irwin, Elliott, Fagan, and Hansen, 2001;MacKenzie, 2000;Izzo and Ross, 1990;Andrews 1990, Ross andFabiano, 1985;Garrett, 1985). In several cases this conclusion is quite strong, for example, Izzo and Ross (1990) found that programs containing a cognitive element were twice as effective as those that did not.…”
Section: Resultsmentioning
confidence: 99%
“…For both adults and juveniles, confidence in treatment and rehabilitation began high, but unintended outcomes and a subsequent lack of faith in the system prompted critics to pronounce, "nothing works" (Martinson, 1974). Not all researchers accepted this proclamation, however, and several studies have shown that under the correct conditions, treatment and rehabilitation can have positive effects on reducing delinquency (Lipsey, 1992;Izzo and Ross, 1990;Gendreau and Ross, 1987;Garrett, 1985). Research has identified several of these conditions that provide effective treatment of juveniles, with ensuing reductions in violence and delinquency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in this domain have provided various evidence based strategies to deal with Juvenile delinquency, which highly focuses on approaches involving Family Therapy Group Therapy has also been carried out in various groups of Children in Conflict with Law [41,42]. Social skills training modules are quite effective as well [43][44][45][46]. Some studies have focused on the application of certain Behaviour Therapy techniques [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The consensus amongst more contemporary penologists and psychologists (e.g. Andrews, 1995;Andrews, Zinger, Hodge, Gendreau & Cullen, 1990;Cann, Falshaw, Nugent & Friendship, 2003;Dowden & Andrews, 1999;Falshaw, Friendship, Travers & Nugent, 2003;Garrett, 1985;Hollin & Palmer, 2009;Izzo & Ross, 1990;Lipsey, 1992;Lipsey, Chapman & Landenberger, 2001;Lipton, Martinson & Wilks, 1975;McGuire & Priestley, 1995;Polaschek et al (2005); Tong & Farrington, 2006;Wexler, Falkin &Lipton, 1990 andLab, 1989) is, that through the correct identification and targeting of an offender"s specific criminogenic (offence related) psychological determinants, and the implementation of appropriately targeted cognitive behavioural interventions, the likelihood of that offender reducing their proclivity for antisocial conduct is significantly increased.…”
Section: The Evolution Of Rehabilitative Treatmentmentioning
confidence: 99%